Aplikasi Modul Evaporative Cooling Aktif Pada AC Split 1 PK - Ahmad Wisnu Sulaiman; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The commonly used air conditioning system is the air conditioning system with vapor compression cycle. However, vapour compression cycle has an operation problem, which is the high energy consumption caused by air cooled condenser type. The condensors disadventages is temperature will increase when ambient temperature increases, it reduced the heat rejected by condenser. This studies used evaporative cooler moduleon condenser inlet to reduce the entering air temperature. The module efect on standard vapour compression cycle performance was tested using experimental methods by testing the effect of water discharged (0.88, 1.04, 1.2 L/min) with the power input. The result showed standard cycle power input with 2000 W cooling load is 0.586186 kW, and the lowest power input of a modification cycle is 0.547665 kW with water discharged 1.2 L/min.Keywords : Evaporative Cooler, Power input, Heat rejection, Condenser